2021
DOI: 10.5534/wjmh.200085
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Cavernous Veno-Occlusive Function through Chronic Administration of a Jun-Amino Terminal Kinase Inhibitor and a LIM-Kinase 2 Inhibitor by Suppressing Cavernous Apoptosis and Fibrosis in a Rat Model of Cavernous Nerve Injury: A Comparison with a Phosphodiesterase Type 5 Inhibitor

Abstract: Purpose To determine if chronic administration of Jun-amino terminal kinase (JNK)-inhibitors and LIM-kinase 2 (LIMK2)-inhibitors from the immediate post-injury period in a rat model of cavernous-nerve-crush-injury could normalize cavernous-veno-occlusive-function, and to compare it with phosphodiesterase type 5 (PDE5)-inhibitors. Materials and Methods A total of 75 12-week-old male Sprague–Dawley-rats were randomized into five groups: sham-surgery (S), cavernous-nerve-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Although molecular pathways of cavernosal apoptosis induced by CN injuries are still poorly understood, several previous studies, including a previous study of ours, have reported that a few apoptotic pathways including Sonic hedgehog, Rho-kinase, and JNK pathways, are involved in cavernosal apoptosis following CN injury [ 24 , 25 , 26 , 27 ]. Under this background, our previous studies reported that JNK pathway inhibition, which was known to play a critical role in apoptosis through both nucleus- targeted and mitochondria-targeted signaling, improved erectile function in a CNCI rat model [ 11 , 14 , 15 , 28 ]. However, we thought that both anti-apoptotic and regenerative treatment would be needed to completely preserve the structural integrity of the penis and to recover from CN injury-induced ED, given that the treatment alone for suppressing the structural alterations (apoptosis, fibrosis, or both) of the corpus cavernosum did not normalize erectile function in a CN injury rat model, according to our previous studies [ 11 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although molecular pathways of cavernosal apoptosis induced by CN injuries are still poorly understood, several previous studies, including a previous study of ours, have reported that a few apoptotic pathways including Sonic hedgehog, Rho-kinase, and JNK pathways, are involved in cavernosal apoptosis following CN injury [ 24 , 25 , 26 , 27 ]. Under this background, our previous studies reported that JNK pathway inhibition, which was known to play a critical role in apoptosis through both nucleus- targeted and mitochondria-targeted signaling, improved erectile function in a CNCI rat model [ 11 , 14 , 15 , 28 ]. However, we thought that both anti-apoptotic and regenerative treatment would be needed to completely preserve the structural integrity of the penis and to recover from CN injury-induced ED, given that the treatment alone for suppressing the structural alterations (apoptosis, fibrosis, or both) of the corpus cavernosum did not normalize erectile function in a CN injury rat model, according to our previous studies [ 11 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under this background, our previous studies reported that JNK pathway inhibition, which was known to play a critical role in apoptosis through both nucleus- targeted and mitochondria-targeted signaling, improved erectile function in a CNCI rat model [ 11 , 14 , 15 , 28 ]. However, we thought that both anti-apoptotic and regenerative treatment would be needed to completely preserve the structural integrity of the penis and to recover from CN injury-induced ED, given that the treatment alone for suppressing the structural alterations (apoptosis, fibrosis, or both) of the corpus cavernosum did not normalize erectile function in a CN injury rat model, according to our previous studies [ 11 , 14 , 15 ]. In accordance with this hypothesis, the present study showed that treatment with a JNK inhibitor alone for two weeks starting in the immediate postinjury period partially restored PECAM-1 protein expression, eNOS phosphorylation, and the erectile response to electrostimulation in a CNCI-induced ED rat model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations